Identification of mutagenic metabolites of benzo(a)pyrene in mammalian cells. - Huberman, E (1976)
The mutagenicity of benzo[a]pyrene and 15 of its derivatives, which included phenols, the benzo[a]yrene-4,5-epoxide (the K-region epoxide), dihydrodiols, two isomeric 7,8-diol-9,10-epoxides, a 6-methyl derivative, and a 6-hydroxymethyl derivative, were tested with Chinese hamster V79 cells in order to identify the mutagenic metabolites of benzo[a]pyrene. Mutations were characterized by resistance to ouabain or 8-azaguanine. Since V79 cells do not metabolize polycyclic hydrocarbons, mutagenesis was tested both in the presence and absence of benzo[a]pyrene-metabolizing normal golden hamster cells. All the tested phenols, 4,5-diols, trans-9,10-diol, 6-methyl, and 6-hydroxymethyl derivatives of benzo[a]pyrene showed little or no mutagenicity for both genetic markers. The (+/-)7alpha,8beta-dihydroxy-9alpha,10alpha-epoxy-7,8;9,10-tetrahydrobenzo[a]pyrene and K-region 4,5-epoxide exhibited similar and moderate mutagenicity in the absence of benzo[a]pyrene-metabolizing cells, but the (+/-)7alpha,8beta-dihydroxy-9beta,10beta-epoxy-7,8,9,10-tetrahydrobenzo[a]-pyrene showed a 2000- and 270-fold higher mutation frequency for ouabain and 8-azaguanine resistance, respectively, than did the K-region 4,5-epoxide. The trans-7,8-diol which was not mutagenic in the absence of benzo[a]pyrene-metabolizing cells was more mutagenic than benzo[a]pyrene after metabolism and mutagenesis by trans-7,8-diol in these cells was inhibited by 7,8-benzoflavone, an inhibitor of mixed-function oxidases. Metabolically formed trans-7,8-diol was isolated and incubated with rat liver microsomes in the presence of co-factors. High-pressure liquid chromatography analysis indicated that the major metabolite of trans-7,8-diol is 7alpha,8beta-dihydroxy-9beta,10beta-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene. The results indicate that the latter compound is metabolically formed and the major mutagenic intermediate of benzo[a]yrene metabolism.